China-Pakistan Economic Corridor: Role of Teachers in Career Counseling of Students at Higher Education Level - Ghulam Fatima; Misbah Malik; Rukhsana Bashir; Noreen Rafiq (Journal of Business and Social Review in Emerging Economies, 2020)
China-Pakistan Economic Corridor (CPEC) is a blessing for Pakistan and China. China Pakistan Economic Corridor (CPEC) appears as a major ‘Prosperity Tool’ which can help Pakistan to overcome its economic problems. CPEC has been researched up till now in various trade and commerce fields but its most important linkage with education was hard to find. This study was aimed to identify the role of university teachers in developing awareness and providing guidance and counseling to their students regarding career opportunities existing in the projects of CPEC. All the teachers of public and private universities of city Lahore were the population of the study. A sample of 150 teachers was selected randomly from different departments of two public and two private universities of city Lahore. A self-developed and validated instrument was used to identify the role of teachers. Reliability index (Chronbach Alpha) of the instrument was α= .82. Results showed that teachers were playing their role to make students aware of the CPEC projects. They were also providing counseling informally to their students at higher education level regarding the career opportunities existing in the CPEC projects. There was no significant difference found in the role of teachers in providing career counseling to their students at higher education level about CPEC projects with respect to their gender, residential area, type of university, designation and years of working experience. It was recommended that universities should arrange seminars, workshops, conferences, panel discussions and brainstorming sessions for the sensitization of their faculty members so that they could create awareness among their students regarding CPEC and take measures for their career counseling.